Nature and distribution of slab‐derived fluids and mantle sources beneath the Southeast Mariana forearc rift. (9th October 2013) - Ribeiro, Julia M.; Stern, Robert J.; Kelley, Katherine A.; Martinez, Fernando; Ishizuka, Osamu; Manton, William I.; Ohara, Yasuhiko
<x xml:space="preserve">Abstract</x> [1] Subduction zone magmas are produced by melting depleted mantle metasomatized by fluids released from the subducted slab. In most subduction zones, formation of backarc basin (BAB) and arc magmas depletes the mantle source toward the trench, resulting in more depleted mantle beneath the forearc. Slab‐derived fluids are aqueous beneath the forearc where the slab dehydrates, and the deeper subduction component is increasingly dominated by sediment melt at ≥100 km depth. In this study, we present new data for the Southeast Mariana forearc rift (SEMFR), an unusual region of forearc igneous activity, where 2.7–3.7 Ma lavas were recovered by Shinkai 6500 diving and dredged during the TN273 Thomas Thompson cruise. SEMFR is divided into SE (near the trench) and NW (near the arc) sectors. NW SEMFR lavas and glassy rinds are more depleted in melt‐mobile elements (e.g., Nb and Yb) and more enriched in fluid‐mobile elements (e.g., Cs, Rb, and Ba). SEMFR lavas were produced by partial melting of a BAB‐like mantle source, metasomatized by sediment melt and aqueous fluids released from dehydrating the subducted oceanic crust, and the forearc serpentinized peridotites. Evidence of sediment melt, even in SE SEMFR lavas, could be explained by inheritance of BAB‐like Th/Nb in the SEMFR mantle source. Geochemical mapping demonstrates that the subduction components and mantle depletion increase towards the arc, suggesting (i) input of a less‐depleted mantle beneath SE SEMFR that flowed toward the arc and (ii) aqueous slab‐derived fluids become increasingly important at ∼50–100 km depth, reflecting that phengite and barite from the downgoing plate and forearc serpentinite broke down beneath the arc volcanoes.